Kardiochirurgia dorosłychCoronary-subclavian steal syndrome after CABG treated by stent implantation into the left subclavian artery: should coronary angiography routinely show the left internal thoracic ar-tery? - Bartczak, Karol; Walczak, Andrzej; Jander, Slawomir; Banyś, Andrzej; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The use of the left internal thoracic artery (LITA) has been a golden standard in surgical revascularization of myocardium. Analyzing a case of a 52-year-old woman operated non- electively due to the left main stem stenosis with undiagnosed stenosis of the left subclavian artery, the authors try to answer the question if LITA should be routinely shown on coronary angiography. Due to the worsening clinical state after coronary artery by-pass grafting (CABG), the patient was taken back to the cath lab for the re-do angiography. It revealed a critical stenosis of the left subclavian artery, which was managed by stent implantation. This treatment brought relief from angina and neurological signs.